Formulation and Evaluation of Physical Quality of Peel-Oof Masks of Essential Oils of Galam Kalimantan Plants - Ayuchecaria, Noverda; Karelius, Karelius; Rosmainar, Lilis; Aryzki, Saftia (Fakultas Kedokteran Universitas Lambung Mangkurat, 2024)
The Kalimantan galam plant (Melaleuca cajuputi subsp cajuputi) has been used for generations but its use is very limited, only as wooden piles which form the basis of buildings in swamps (cerucuk), pillars for building construction, stakes (supports for newly planted seedlings) and siring. Street. The use of galam essential oil as an active ingredient in peel-off mask preparations can be efficacious in reducing inflammation and infection of acne or other skin problems. Facial masks in the form of peel-off itself have many advantages, namely their practical use and are easy to remove or lift like elastic membranes compared to conventional masks which leave residue. This study aims to design a peel-off mask formulation by utilizing the active ingredient in the essential oil of the galam plant. The preparations were then tested for physical quality requirements including organoleptic tests, homogeneity tests, pH tests, drying time tests, spreadability and adhesion tests. The results of the tests that have been carried out include the extraction of essential oils as the active substance. The yield of essential oil obtained was 0.12%. Organoleptic quality tests showed changes in color, smell and shape in the three formulations. The homogeneity test for formulas I and II remained homogeneous, while for formula III the consistency changed to 2 layers. The pH test showed that all formulations met the pH requirements for topical preparations, namely 4-8. The drying time test for formula I was more difficult to remove, formula II was not too stiff while formula III was stiffer. Spreadability test on formulas I, II and III 5-7 cm. The gel viscosity test decreased and the adhesion test on formulation I was easily released, formulas II and III were not easily released while the irritation test of 30 people did not experience redness in 3 formulas.